2020
DOI: 10.2478/bsrj-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Use of Balanced Scorecard and Data Envelopment Analysis in the Banking Industry

Abstract: Background: Starting from the limitations of different single-method approaches to measuring the organizational efficiency, the paper is focused on covering both the financial and non-financial factors of this concept by combining two methods, namely the Balanced Scorecard (BSC) and Data Envelopment Analysis (DEA).Objectives: The main goal of the research in the paper is to show that certain deficiencies in the independent application of each method are eliminated by combining these methods.Methods/Approach: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The study revealed that the best way to evaluate performance management in banks is to use the four perspectives of the BSC. Bošković and Krstić (2020) conducted research to examine the combined use of the BSC and Data Envelopment Analysis in banking. The results of the study revealed that if the BSC is used first in application followed by the CEA model, leaders can effectively measure performance in a bank.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study revealed that the best way to evaluate performance management in banks is to use the four perspectives of the BSC. Bošković and Krstić (2020) conducted research to examine the combined use of the BSC and Data Envelopment Analysis in banking. The results of the study revealed that if the BSC is used first in application followed by the CEA model, leaders can effectively measure performance in a bank.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research also introduced the collaboration of two algorithms, Naïve Bays and Random Forest, with text analysis methods for messages' classification to be wither extreme or moderate. More recently, another perspective which highlighted the effectiveness of applying business intelligence tools in the banking sectors is presented in (Bošković & Krstić, 2020). The research presents the contribution of business scorecards tool and data envelopment analysis approach in identifying the business goals and track the organizational business progress.…”
Section: Applications Of Data Mining In Bankingmentioning
confidence: 99%
“…Some studies [77,78] have proposed a BSC-DEA model to measure organizational efficiency in the banking industry. Akman and Turan [79] presented an expanded BSC structure for banks by adding risk and agile perspectives to the current BSC structure.…”
Section: Introductionmentioning
confidence: 99%